FACTORS CONTROLLING URANIUM GEOCHEMISTRY IN THE MIXING ZONE OF RIVER- AND SEAWATERS - Savenko A.V. (My University, 2007)
When the transformations of the continental runoff in river mouths is studied, much attention is paid to the radioloecological aspect of the problem, in particular, to the identification of factors controlling the migration of radionuclides at the river–sea geochemical barrier. For trace elements with relatively low biological accumulation coefficients, a significant role is played by sorption–desorption processes, which are responsible for the redistribution of solute and particulate modes, because zones where riverine and marine waters are mixed are characterized by drastic changes in the concentrations of dissolved components and coupled changes in the composition of the adsorbed complex of riverine suspensions.